2015
DOI: 10.1021/jacs.5b05384
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-Specific Growth of Semiconducting SWNT Arrays Using Uniform Mo2C Solid Catalyst

Abstract: Semiconducting single-walled nanotube (s-SWNT) arrays with specific diameters are urgently demanded in the applications in nanoelectronic devices. Herein, we reported that by using uniform Mo2C solid catalyst, aligned s-SWNT (∼90%) arrays with narrow-diameter distribution (∼85% between 1.0 and 1.3 nm) on quartz substrate can be obtained. Mo2C nanoparticles with monodisperse sizes were prepared by using molybdenum oxide-based giant clusters, (NH4)42[Mo132O372(H3CCOO)30(H2O)72]·10H3CCOONH4·300H2O(Mo132), as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 22 publications
0
70
0
Order By: Relevance
“…The excessive growth temperatures required with FeMoC appear to counter previous work with Fe-Mo catalyst systems demonstrating CNT growth at temperatures as low as 550°C [22][23][24]. It should be noted that both Fe and Mo have been shown to be efficient catalysts both independently and as mixed metal nanoparticles [25][26][27][28][29][30]; thus, FeMoC should be ''active'' for CNT growth, but under the prior growth conditions studied it is not [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 78%
“…The excessive growth temperatures required with FeMoC appear to counter previous work with Fe-Mo catalyst systems demonstrating CNT growth at temperatures as low as 550°C [22][23][24]. It should be noted that both Fe and Mo have been shown to be efficient catalysts both independently and as mixed metal nanoparticles [25][26][27][28][29][30]; thus, FeMoC should be ''active'' for CNT growth, but under the prior growth conditions studied it is not [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 78%
“…Since then, chirality selective growth of SWCNTs was succeeded on a number of different catalysts: CoMo [106108], FeCo [109], FeRu [110], NiFe [111], Co [112114], FeCu [115], Au [116], CoMn [117], Ni [118], Fe [119120], CoPt [121], Co x Mg 1−x O [122], CoSO 4 [123], WCo alloy [124125] and Mo 2 C [126]. SiO 2 or MgO were used as catalyst support.…”
Section: Reviewmentioning
confidence: 99%
“…SiO 2 or MgO were used as catalyst support. The synthesis was conducted using different carbon precursors: CO [105108 112115 117119 122123], C 2 H 5 OH [107,109,120121 124126], CH 3 OH [107], CH 4 [110,116] and C 2 H 2 [111]. Table 1 summarizes the reports on the chirality selective synthesis of SWCNTs.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of 25 Fe atoms to FeMoC through coordination would suggest that 139 atoms are sufficient, but 114 are not. When considering that both Mo and Fe have demonstrated effective catalytic performance both independently and as mixed heterogenous nanoparticles [19][20][21][22], FeMoC should be catalytically active, but under the growth conditions reported in prior work it is not [16,17,23,24]. We have recently shown that this is in part due to both incomplete catalyst activation and the sublimation of a portion of the Mo component during the slow catalyst activation process [25,26].…”
Section: Introductionmentioning
confidence: 99%